Acquired liver fat is a key determinant of serum lipid alterations in healthy monozygotic twins. (21st May 2013) - Kaye, S.M.; Maranghi, M.; Bogl, L.H.; Kaprio, J.; Hakkarainen, A.; Lundbom, J.; Lundbom, N.; Rissanen, A.; Taskinen, M.‐R.; Pietiläinen, K.H.
<x xml:space="preserve">Abstract</x> Objective: The effects of acquired obesity on lipid profile and lipoprotein composition in rare BMI‐discordant monozygotic (MZ) twin pairs were studied. Design and Methods: Abdominal fat distribution, liver fat (magnetic resonance imaging and spectroscopy), fasting serum lipid profile (ultracentrifugation, gradient gel‐electrophoresis, and colorimetric enzymatic methods), and lifestyle factors (questionnaires and diaries) were assessed in 15 BMI‐discordant (within‐pair difference [Δ] in BMI >3 kg/m2) and nin concordant (ΔBMI <3 kg/m2) MZ twin pairs, identified from two nationwide cohorts of Finnish twins. Results: Despite a strong similarity of MZ twins in lipid parameters (intra‐class correlations 0.42‐0.90, P < 0.05), concentrations of apolipoprotein B (ApoB), intermediate‐density lipoprotein cholesterol, low‐density lipoprotein cholesterol (LDL‐C), high‐density lipoprotein 3a% (HDL3a%), and HDL3c% were higher (P < 0.05) and those of HDL cholesterol, HDL2‐C, and HDL2b% were lower (P < 0.01) in the heavier co‐twins of BMI‐discordant pairs. The composition of lipoprotein particles was similar in the co‐twins. When BMI‐discordant pairs were further divided into liver fat‐discordant and concordant (based on median for Δliver fat, 2.6%), the adverse lipid profile was only seen in those heavy co‐twins who also had high liver fat. Conversely, BMI‐discordant pairs concordant for liver fat did not differ significantly in lipid parameters. In multivariate analyses controlling for Δsubcutaneous, Δintra‐abdominal fat, sex, Δsmoking and Δphysical activity, Δliver fat was the only independent variable explaining the variation in ΔApoB, Δtotal cholesterol, and ΔLDL‐C concentration. Conclusions: Several pro‐atherogenic changes in the amounts of lipids but not in the composition of lipoprotein particles were observed in acquired obesity. In particular, accumulation of liver fat was associated with lipid disturbances, independent of genetic effects.